2012
DOI: 10.1088/0029-5515/52/6/063013
|View full text |Cite
|
Sign up to set email alerts
|

Physics of intrinsic rotation in flux-driven ITG turbulence

Abstract: Abstract. Global, heat flux-driven ITG gyrokinetic simulations which manifest the formation of macroscopic, mean toroidal flow profiles with peak thermal Mach number 0.05, are reported. Both a particle-in-cell (XGC1p) and a semi-Lagrangian (Gysela) approach are utilized without a priori assumptions of scale-separation between turbulence and mean fields. Flux-driven ITG simulations with different edge flow boundary conditions show in both approaches the development of net unidirectional intrinsic rotation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…(20). It indicates that a turbulence intensity gradient naturally arises because A 1 and A 2 contain mean plasma profiles.…”
Section: Formulationmentioning
confidence: 97%
See 1 more Smart Citation
“…(20). It indicates that a turbulence intensity gradient naturally arises because A 1 and A 2 contain mean plasma profiles.…”
Section: Formulationmentioning
confidence: 97%
“…The process of hk k i symmetry breaking by E Â B shear and/or intensity gradient implies a coupling between intrinsic rotation and transport barrier dynamics, such as internal transport barrier (ITB) formation, which involves steep temperature and/or density gradients (i.e., strong radial inhomogeneity) and the strong E Â B shear and/or the fluctuation intensity gradient (i.e., hk k i symmetry breaking). Gyrokinetic simulations have shown the generation of intrinsic rotation from the hk k i symmetry breaking by mean E Â B shear [20][21][22][23] and turbulence intensity gradient 20 and up-down asymmetry of equilibrium magnetic topology. 24,25 Gyrokinetic simulations have also shown residual stress from profile shearing effects.…”
Section: Introductionmentioning
confidence: 99%
“…(3) and (18) are required; a dedicated study of intrinsic rotation with both GYSELA and XGC1 is to be reported elsewhere. 79,80 A careful accounting of collisions is also important to correctly describe the residual level of the low frequency turbulence-induced axisymmetric sheared E Â B mean and zonal flows. The importance of such flows, linearly damped through collisions alone and which dynamically participate in turbulence self-regulation has long been emphasised.…”
Section: Discussion: Which Physics Can We Address?mentioning
confidence: 99%
“…In contrast, here we show that edge and core flows are coupled via the propagation of fluctuation momentum from the edge region into the core region, via a nonlocal process such as turbulence spreading, avalanches, etc. [10][11][12]. Typically, tokamak plasmas become more turbulent towards the edge with increasing turbulence amplitude [13].…”
mentioning
confidence: 99%